Role models in Hungarian educational decrees between the two world wars (1920-1938) - Dergez , Ildikó (Tudásmenedzsment, 2023)
The study presents the diverse types of role models that appeared in Hungarian educational decrees between 1920 and 1938. These documents can be found in the official educational journal of “Hivatalos Közlöny” (“Hungarian Gazette”), which functionated as the main form of communication between the Royal Hungarian Ministry of Religious Affairs and Public Education and the educational branch. It is an essential fact that we do not only find historical examples but also literary and thematic examples of the period. Many of these role models were historic figures such as kings, princes, and other noble people. The next category consisted of famous figures of Hungarian and Latin literature like János Arany, Sándor Petőfi and Horatius. Nevertheless, there were role models outside this typical “historical” spectrum, like thematic days and memorials of fallen soldiers.